WHO Handbook on Indoor Radon : a Public Health Perspective. - Organization, World Health (World Health Organization, 2009)
""The WHO Handbook on Indoor Radon"" is a key product of the WHO International Radon Project, which was launched in 2005. The ""Handbook"" focuses on residential radon exposure from a public health point of view and provides detailed recommendations on reducing health risks from radon and sound policy options for preventing and mitigating radon exposure. The material in the ""Handbook"" reflects the epidemiological evidence that indoor radon exposure is responsible for a substantial number of lung cancers in the general population. The material is organized into six chapters, each introduced b.